Polyaniline cryogels: Biocompatibility of novel conducting macroporous material - Humpolíček, Petr; Radaszkiewicz, Katarzyna Anna; Capáková, Zdenka; Pacherník, Jiří; Bober, Patrycja; Kašpárková, Věra; Rejmontová, Petra; Lehocký, Marián; Ponížil, Petr; Stejskal, Jaroslav (Scientific reports, 2018)
Polyaniline cryogel is a new unique form of polyaniline combining intrinsic electrical conductivity and the material properties of hydrogels. It is prepared by the polymerization of aniline in frozen poly(vinyl alcohol) solutions. The biocompatibility of macroporous polyaniline cryogel was demonstrated by testing its cytotoxicity on mouse embryonic fibroblasts and via the test of embryotoxicity based on the formation of beating foci within spontaneous differentiating embryonic stem cells. Good biocompatibility was related to low contents of low-molecular-weight impurities in polyaniline cryogel, which was confirmed by liquid chromatography. The adhesion and growth of embryonic stem cells, embryoid bodies, cardiomyocytes, and neural progenitors prove that polyaniline cryogel has the potential to be used as a carrier for cells in tissue engineering or bio-sensing. The surface energy as well as the elasticity and porosity of cryogel mimic tissue properties. Polyaniline cryogel can therefore be applied in bio-sensing or regenerative medicine in general, and mainly in the tissue engineering of electrically excitable tissues.
Keywords: testování materiálů; Biocompatible Materials; viabilita buněk; Mechanical Phenomena; Materials Testing; aniliny; vysokoúčinná kapalinová chromatografie; myši; Mice; kryogely; Elastic Modulus; Electric Conductivity; Tissue Engineering; Animals; elektrická vodivost; Cryogels; Porosity; teoretické modely; biokompatibilní materiály; tkáňové inženýrství; fibroblasty; zvířata; Cell Culture Techniques; Cell Survival; Fibroblasts; Aniline Compounds; algoritmy; modul pružnosti; poréznost; buněčné kultury; Chromatography, High Pressure Liquid; Models, Theoretical; mechanické jevy; Algorithms